"Automotive repairs, data accessibility, and privacy and security challenges: A stakeholder analysis and proposed policy solutions". (November 2022) - Hemphill, Thomas A.; Longstreet, Phil; Banerjee, Syagnik
Abstract: This article focuses on how the automotive industry effectively manages the data accessibility issue for third-party vehicle repairs. First, the article reviews the key definitions and concepts that make up stakeholder theory and applies it to the automotive industry, and by employing a stakeholder synthesis approach, identifies primary and secondary stakeholders and their economic and political "stakes" in the issue. Second, it presents an analysis of the automotive industry's economic, legal/regulatory/ethical, and technical opportunities and challenges associated with data accessibility. Third, it offers a set of recommended business and public policy proposals useful in resolving the data accessibility issue necessary for the safe and effective repair of automobiles by both retail automotive dealers and independent automotive repair shops. Lastly, following a summary of business and public policy proposals, a discussion of broader applications of data accessibility, security, and privacy in the era of the Internet of Things concludes the article. Highlights: A Massachusetts law requires automotive repair shops access to personal customer data. This law is being litigated in federal district court. This issue has ramifications for access to consumer data, privacy and safety issues. The paper offers a set of proposed business and public policy solutions.